2010
DOI: 10.1177/0018726710365090
|View full text |Cite
|
Sign up to set email alerts
|

A multiple climates approach to understanding business unit effectiveness

Abstract: We propose four theoretically competing climates that are important for businessunit performance: climates for external control, internal control, internal flexibility, and external flexibility. Using a sub-sample of 620 business units from multiple companies across different industries and countries, we identified mechanisms by which climates influence business performance, accounting for different stakeholder interests. Climate for external control related directly to perceived business performance; climates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 120 publications
1
14
0
1
Order By: Relevance
“…This finding reflects the problematic relationship between micro‐ and macro‐performance as spotted recently in the context of organizational climate (e.g. MacCormick and Parker 2010). We therefore suggest that the impact of organizational climate on micro‐performance of public schools is stronger from its impact on macro‐performance in such environments.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…This finding reflects the problematic relationship between micro‐ and macro‐performance as spotted recently in the context of organizational climate (e.g. MacCormick and Parker 2010). We therefore suggest that the impact of organizational climate on micro‐performance of public schools is stronger from its impact on macro‐performance in such environments.…”
Section: Resultssupporting
confidence: 52%
“…One important aspect of organizational climate research is its multi‐dimensionality (MacCormick and Parker 2010). Whereas early writing on organizational climate treated it as a uni‐dimensional factor, later and more recent studies are quite univocal in adopting the multiple‐climate perspective.…”
Section: Pieces In the Puzzle: Background And Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, however, the need for organizations to accommodate competing demands, rather than choosing one before the other, has been increasingly acknowledged. MacCormick and Parker (2010) found that four climate types specified through the competing values framework (CVF, presented further below; Quinn & Rohrbaugh, 1983) had different impacts on customer loyalty, business performance, and staff engagement. Their results supported an emerging shift of focus in organizational research, from studying trade-offs between contrasting phenomena in an either/or perspective, to perspectives open to paradox, both/and.…”
Section: Theoretical Framework and Related Literaturementioning
confidence: 99%
“…In this context, the skills, abilities and the knowledge of an employee within the context of the organizational climate is a crucial factor that may render an organization to succeed in their entrepreneurial abilities. Nevertheless, the effects of various organizational climates on individual-level employee outcomes have been surprisingly under-researched (MacCormick and Parker, 2010). There is little research output on how such initiatives have been affected by the organizational climate within the hotels.…”
mentioning
confidence: 99%